The Forgotten Innate Immune Cells: Unraveling Their Prospective Interactions with Nanomaterials - González-Fernández Á; Maietta I (International Journal of Nanomedicine, 2025)
África González-Fernández,1,2 Immacolata Maietta1,2 1CINBIO, Universidade de Vigo, Vigo, 36310, Spain; 2Immunology Group, Galicia Sur Health Research Institute (IIS Galicia Sur). SERGAS-UVIGO, Vigo, Pontevedra, 36312, SpainCorrespondence: África González-Fernández, CINBIO, Universidade de Vigo, Vigo, 36310, Spain, Tel +34-986-130141, Email africa@uvigo.esAbstract: Nanomaterials, particularly nanoparticles, are revolutionizing various fields, including medicine, due to their distinctive physicochemical properties. Their large surface area, charge and high particle number per unit mass enable enhanced interactions with biological systems, particularly with the immune system. The interaction between nanomaterials and immune cells can influence immune responses in several ways, including modulating cell activation through interactions with pattern recognition receptors (PRRs), internalization, degradation, or accumulation in phagocytic cells, as well as altering the immune microenvironment through the release of granular contents, cytokines, and chemokines. Although many studies have focused primarily on phagocytic (macrophages, dendritic cells, and neutrophils) and Natural killer (NK) cells, less attention has been given to other innate immune cells such as eosinophils, basophils, and mast cells. This review aims to highlight the role of these “forgotten” innate immune cells, providing insights into their function, available cell lines, applicable techniques to understand interactions with nanomaterials, and relevant in vitro and in vivo models.Keywords: eosinophils, basophils, mast cells, nanotechnology, immunogenicity, interaction